Factors affecting use of e-learning platform (SPeCTRUM) among University students in Malaysia - Ghavifekr, S.; Mahmood, H. (Springer, 2017)
Guided by the current need in equipping young minds with the 21st century skills, integration of Information Communication Technology (ICT) in education has changed the way of teaching and learning takes place in educational institutions. The need of fast delivery of knowledge and information, whenever and wherever, has been the catalyst to the growth of e-learning worldwide. In Malaysia, e-learning has been pioneered by the private universities and has been adopted in most universities ever since. In the setting of a research university in Kuala Lumpur, Malaysia , a quantitative design was conducted to investigate the factors affecting the usage of e-Learning platform so called SPeCTRUM by the students. Total of 110 respondents consist of undergraduate and postgraduate students from Faculty of Education have been selected randomly to participate in this research. Findings indicate that the co-participatory activities are one the main factors in the motivation of using SPeCTRUM. It was also found that demographic factors of the participants also played a key role in the rate of usage for the e-learning platform.